Analysis of human leukocyte antigen allele polymorphism in patients with non alcoholic fatty liver disease. Issue 32 (August 2019) - Karrar, Azza; Hariharan, Siddharth; Fazel, Yousef; Moosvi, Ali; Houry, Mohamad; Younoszai, Zahra; Jeffers, Thomas; Zheng, Li; Munkhzul, Otgonsuren; Hunt, Sharon; Monge, Fanny; Goodman, Zachary; et al.
Abstract : Abstract: The human leukocyte antigen (HLA) genes may play a role in the pathogenesis of non-alcoholic fatty liver disease (NAFLD) and its progressive form, non-alcoholic steatohepatitis (NASH). The aim of this study was to assess the association of HLA class I and II alleles with NASH and its histological features. Deoxyribonucleic acid (DNA) was extracted from 140 subjects (85 biopsy-proven NAFLD and 55 controls) and genotyped for HLA (-A, -B, -C, -DR1, -DR3, -DQ, and -DP). Liver biopsies were assessed for presence of NASH, degree of fibrosis and inflammation. Multivariate analysis was performed to assess associations between HLA genes and different histologic features of NAFLD. Our data for HLA class I showed that HLA-C*4 was associated with lower risk for histologic NASH and HLA-C*6 was protective against portal fibrosis. Conversely, HLA-B*27 was associated with high-grade hepatic steatosis, while HLA-A*31 was associated with increased risk for advanced fibrosis. Among HLA class II alleles, HLA-DQA1*01 was associated with lower risk for NASH while HLA-DRB1*03 was associated with increased risk for NASH. Our findings indicate that HLA class I and II gene polymorphism may be associated with susceptibility to NASH, fibrosis and other pathologic features and may be involved in the pathogenesis of NAFLD.